Analytical Investigation of The Performance of Fluid Viscous Damper and Lead Rubber Bearing Isolator on A Multi-Storey Building - Singha, Badhon; Chowdhury, Nafis Niaz; Sakib, Mohammad Atiqur Rahman (Institut Teknologi Sepuluh Nopember, 2025)
Earthquakes are devastating natural events that can cause substantial structural damage, often resulting in collapses due to inadequate seismic design. This study investigates the effectiveness of two seismic protection systems: fluid viscous damper (FVD) and lead rubber bearing (LRB) isolation, in improving the seismic performance of a structure. The initial research did not include any base isolator or link damper for earthquake protection. The results were then compared to a similar investigation of the same structure using FVD and LRB isolation. Significant differences in structural behavior were observed, with both systems demonstrating improved performance in mitigating seismic forces. The findings highlight the importance of incorporating advanced damping mechanisms, such as FVD and LRB, in building design to enhance earthquake resilience in prone regions. This study underscores the critical need for integrating such seismic protection systems to reduce structural damage and improve safety during earthquakes.